2013
DOI: 10.1111/jam.12405
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of ruminal bacterial community in dairy calves from birth to weaning is sequential

Abstract: Aim: Establishment of ruminal bacterial community in dairy calves. Methods and Results: Rumen bacterial community was analysed on 6 calves bred according to commercial practices from day one to weaning at day 83 of age, using 454 16S rRNA-based pyrosequencing. Samples taken at day 1 did not produce amplicons. Analysis of data revealed a three-stage implantation process with a progressive but important shift of composition. At day 2, the bacterial community was mainly composed of Proteobacteria (70%) and Bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

45
270
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(322 citation statements)
references
References 35 publications
(66 reference statements)
45
270
0
7
Order By: Relevance
“…Previous large-scale sequencing work with calves has shown that the bacterial community converges on an "adult" profile as the calves age, and in particular, as they are fed increasing percentages of dietary roughage (4). The idea of a stable adult ruminal community with only minor, smallscale fluctuations was further supported by a study using wholecommunity fingerprinting of adult cows over the course of 21 days (41).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Previous large-scale sequencing work with calves has shown that the bacterial community converges on an "adult" profile as the calves age, and in particular, as they are fed increasing percentages of dietary roughage (4). The idea of a stable adult ruminal community with only minor, smallscale fluctuations was further supported by a study using wholecommunity fingerprinting of adult cows over the course of 21 days (41).…”
Section: Discussionmentioning
confidence: 59%
“…Investigations into time-dependent changes in the ruminal community have, to date, focused on the first year of life, as during that time the anatomical structure of the preruminant stomach changes rapidly as the calf's diet shifts from protein-and fat-rich milk to cellulose-and starch-rich feed (22). As calves mature, there are major and significant changes in the digestive bacterial population, even at the phylum level, and a general convergence toward an "adult" profile numerically dominated by bacteria in the phyla Firmicutes, Bacteroidetes, and Proteobacteria (4,6,23). The difficulty of defining when an animal is physiologically mature (with respect to lactation) as opposed to sexually mature, the granularity of sampling (6,23), assumptions regarding community similarity when animals are sacrificed (6), and if animals were sampled concurrently instead of sequentially (23) leave unresolved many questions regarding ruminal community dynamics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, most of the alpha diversity indices (except ACE and the Simpson index) increased with age, suggesting that the microbiota in older age groups is more diverse than that in earlier age groups. This is similar to the process of microbial colonization of the rumen contents (11,26).…”
Section: Figmentioning
confidence: 74%
“…Recently, Rey et al (2014) andDe Barbieri et al (2015) have shown that there is a pattern of establishment and that this can be influenced by the species that are initiated into the microbiome soon after birth from maternal or other sources. This is a fascinating field of study opening up the possibility of long-term manipulation of the rumen microbiome.…”
Section: Rumen Efficiency and Rumen Microbiomementioning
confidence: 99%